New methods of teaching and learning in libraries - Gleason, Ann Whitney 1960- (Medical Library Association books, 2017)
New Methods of Teaching and Learning in Libraries is a one-stop introduction to the role of technology in teaching and learning in libraries. Emerging models of library instruction and library support of instruction will be presented. Increasingly, librarians are called upon to partner with educational faculty and community members to deliver content and support innovative educational initiatives. Since libraries reach across academic disciplines and provide resources for the greater community, they are uniquely positioned to provide services and technologies that are available to many, bringing innovation out of silos and facilitating innovation in the community